A Systematic Review of Current Risk Assessment Practices in Construction Projects (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Purpose: This systematic review examines current risk assessment practices in construction projects, analyzing methodological approaches, technological integration, and thematic priorities in literature published between 2020 and 2026. The study aims to identify prevailing risk assessment practices and research gaps while providing a comparative analysis of methodological evolution.Methodology: Following PRISMA guidelines, a systematic literature review was conducted across Scopus, Web of Science, and Dimensions databases. The search targeted peer-reviewed articles on construction project risk assessment published from January 2020 to February 2026. From 847 initial records, 187 articles met inclusion criteria and were analyzed using bibliometric and content analysis methods with inter-reviewer agreement validation.Findings: Analysis reveals quantitative methods dominate (47%), followed by qualitative (32%) and mixed-methods (21%). Current practices comprise traditional techniques (31%), advanced methods including AI and machine learning (37%), hybrid approaches (18%), and real-time assessment (14%). Advanced methods demonstrate 15–25% higher prediction accuracy but face implementation barriers including data requirements and interpretability challenges. Real-time assessment, despite 35–50% accident reduction potential in trials, remains limited due to cost and infrastructure constraints. Significantly, 65% of studies exclude post-construction variables, and developing economies remain underrepresented (24%).Originality: This review provides the first comprehensive synthesis of risk assessment practices spanning 2020-2026, quantifying methodological trends and identifying that 65% of studies lack integration of post-construction variables. The findings establish a baseline for understanding the evolution toward technology-enabled, proactive risk assessment frameworks in construction projects.